Peran Keselamatan dan Kesehatan Kerja ( K3 ) dan Lingkugan Kerja Dalam Meningkatan Produktivitas Kerja Pada PT . DSP - Fauzi, Achmad; Pramukty, Rachmat (Jurnal Dinamika Manajemen, 2024)
This study aims to analyze the role of safety and health ( K3 ) and the work environment in increasing work productivity at PT . DSP. Informants in this study were production employees totaling 5 people. Data was collected by distributing questionnaires with snowball sampling technique. The data analysis method used descriptive qualitative method. The results of the study showed that the role of occupational safety and health, and the work environment and work productivity had been carried out well, seen from the results of the informants' answers stating the need for K3 supported by good equipment and a good environment. And work safety protocols to support the success of production.